(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The word-formation structure of the names of birds of the begining of a 20 century is analysed in the article (on the material of B. D. Grinchenko’s Ukrainian dictionary), the basic metods of creation of these zooleksem are certained, their word-formation feature and productivity of word-formation types are set.